Bilateral Maps for Partial Matching. (2nd April 2013) - van Kaick, Oliver; Zhang, Hao; Hamarneh, Ghassan
<x xml:space="preserve">Abstract</x> Feature‐driven analysis forms the basis of many shape processing tasks, where detected feature points are characterized by local shape descriptors. Such descriptors have so far been defined to capture regions of interest centered at individual points. Using such regions to compare feature points can be problematic when performing partial shape matching, since the region of interest is typically defined as an isotropic neighborhood around a point, which does not adapt to the geometry of the shape parts. We introduce the bilateral map, a local shape descriptor whose region of interest is defined by two feature points. Compared to the classical descriptor definition using a single point, the bilateral approach exploits the use of a second point to place more constraints on the selection of the spatial context for feature analysis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>